2002
DOI: 10.1017/s0965539502000232
|View full text |Cite
|
Sign up to set email alerts
|

The role of fetal ECG monitoring in labour

Abstract: Objectives: To determine if the degree of caput impacts the accuracy of assessing fetal position in labour when completed by third and fourth year obstetrics residents. Methods: Assessment of fetal position during labour was performed by third and fourth year residents when patients were 8 cm dilated or more, had ruptured membranes, and the gestation was 35 weeks or greater. The residents performed digital examinations for location and axis of fetal sutures and fontanelles in order to determine the orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…However, the specificity of the PR/RR ratio as a marker for hypoxia and acidemia has been disputed (15). While the decrease in PR/RR ratio during UCO was clear, Westgate et al (15) concluded that under conditions of no or only mild acidosis a decrease in PR/RR ratio was a marker of reflex responses to HR decelerations and that it did not provide additional information concerning the metabolic reserves of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specificity of the PR/RR ratio as a marker for hypoxia and acidemia has been disputed (15). While the decrease in PR/RR ratio during UCO was clear, Westgate et al (15) concluded that under conditions of no or only mild acidosis a decrease in PR/RR ratio was a marker of reflex responses to HR decelerations and that it did not provide additional information concerning the metabolic reserves of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…The FECG consists of the P, QRS and T waves separated by PR and ST intervals. The FECG provides valuable information about the conduction system of the foetus heart (Westgate et al 2002). Foetal heart rate signal which can be constructed from the FECG also provides information about the foetus status by studying the foetal heart rate characteristics such as baseline heart rate, accelerations, decelerations and variability (Guzman andVinzileos 1997, Westgate et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in PR/RR ratio were found to be highly correlated to hypoxia. However the specificity of the PR/RR ratio as a marker for hypoxia and acidosis has been disputed 89 . While the decrease in PR/RR ratio during UCO was clear, Westgate et al concluded that under conditions of no or only mild acidosis a decrease in PR/RR ratio was a marker of reflex responses to heart rate decelerations, and that it did not provide additional information concerning the metabolic reserves of the fetus 89 .…”
Section: Discussionmentioning
confidence: 99%